1964 Democratic National Convention Tally Sheet (1964)
This document is a 1964 Democratic National Convention tally sheet, courtesy of American Airlines, listing each state and territory along with its allocated convention votes. It provides individual vote totals for all states, the District of Columbia, and U.S. territories such as Puerto Rico and Guam. The sheet shows a total of 2,316 convention vote.